Vibrational satellites of C2S, C3S, and C4S: microwave spectral taxonomy as a stepping stone to the millimeter-wave band. Issue 20 (9th May 2018) - McGuire, Brett A.; Martin-Drumel, Marie-Aline; Lee, Kin Long Kelvin; Stanton, John F.; Gottlieb, Carl A.; McCarthy, Michael C.
Abstract : We present a microwave spectral taxonomy study of several hydrocarbon/CS2 discharge mixtures, in which more than 60 distinct species/vibrational states were detected and analyzed. Abstract : We present a microwave spectral taxonomy study of several hydrocarbon/CS2 discharge mixtures in which more than 60 distinct chemical species, their more abundant isotopic species, and/or their vibrationally excited states were detected using chirped-pulse and cavity Fourier-transform microwave spectroscopies. Taken together, in excess of 85 unique variants were detected, including several new isotopic species and more than 25 new vibrationally excited states of C2 S, C3 S, and C4 S, which have been assigned on the basis of published vibration–rotation interaction constants for C3 S, or newly calculated ones for C2 S and C4 S. On the basis of these precise, low-frequency measurements, several vibrationally exited states of C2 S and C3 S were subsequently identified in archival millimeter-wave data in the 253–280 GHz frequency range, ultimately providing highly accurate catalogs for astronomical searches. As part of this work, formation pathways of the two smaller carbon–sulfur chains were investigated using 13 C isotopic spectroscopy, as was their vibrational excitation. The present study illustrates the utility of microwave spectral taxonomy as a tool for complex mixture analysis, and as a powerful and convenient 'stepping stone' to higher frequency measurements in the millimeter and submillimeter bands.